2019
DOI: 10.2298/tsci180904025c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on flow separation characteristics of last stage blade in steam turbine under small volume flow condition

Abstract: The inlet steam flow of steam turbine is obviously reduced and even in the state of small volume flow when the thermal power unit is involved in peak load operation, which greatly influences the safety of steam turbine. The last stage flow field of steam turbine under small volume flow condition is calculated by the CFX to study the formation, development, influencing range, and the variation rule of the flow separation vortex cores. The results show that the flow separation vortices appear near last stage bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…From Figure 8A-D, it can be found that the transitional windage condition of LSAT stage 2 occurs at about 33%M d with almost 40% π tt.d , this mass flow rate of transitional windage condition is similar to the study 13,17,34 in LP steam turbines the last stage during windage, even though LSAT and steam turbines working with different fluid and the ways of causing low load are different. Besides, the sharp decline in η tt of stage 2 during transitional windage is also similar to that in LP steam turbines' last stage.…”
Section: Global Aerodynamic Performancesupporting
confidence: 64%
See 1 more Smart Citation
“…From Figure 8A-D, it can be found that the transitional windage condition of LSAT stage 2 occurs at about 33%M d with almost 40% π tt.d , this mass flow rate of transitional windage condition is similar to the study 13,17,34 in LP steam turbines the last stage during windage, even though LSAT and steam turbines working with different fluid and the ways of causing low load are different. Besides, the sharp decline in η tt of stage 2 during transitional windage is also similar to that in LP steam turbines' last stage.…”
Section: Global Aerodynamic Performancesupporting
confidence: 64%
“…However, there is complex threedimensional flow in rotor passages during windage. As shown in Figure 20B, two distinct vortices can be captured easily and are known as separation vortex and back flow vortex in steam turbine [34][35][36] but their mechanism and characteristic are not exactly the same as that in a steam turbine.…”
Section: The Flow Structure Of Rotors During Windagementioning
confidence: 99%
“…In order to accommodate renewable energy power generation, the coal-fired power generating units are forced to operate for a long time under low mass flow conditions. 1 The operating state of LPC deviates from the design condition for a long time under low mass flow conditions. As the load decreases, the inlet steam mass flow of LPC decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Drózdz (2021) from the view of boundary layer, the relationship between Reynolds number and flow separation is discussed. Cao (2019) studied the effect of flow rate on flow separation of last stage blade of steam turbine. The results show that the flow separation vortices appear near last stage blade at 30% of the rated volume flow.…”
Section: Introductionmentioning
confidence: 99%